A Note on the Methodological Comments - Chung, Kae H. (Academy of Management Journal, 1968)
The article presents a response from Kae H. Chung to a comment from Dr. Goronzy about an earlier article by the author titled ?Developing A Comprehensive Model of Motivation and Performance? in the March 1968 issue of ?Academy of Management Journal.? Goronzy takes issue with the use of statistical techniques in the practice of behavioral science. Chung argues that only with the use of multivariate statistics is the researcher able to develop measurement techniques that permit reliable predictions of human behavior.